Determinants of Mobile Money Adoption - Zeinab Mahmoud (International Telecommunications Society (ITS), 2019)
Mobile Money (MM) services are growing very fast in the developing countries as an important tool for the financial inclusion. Many critical challenges surrounds mobile money services adoption with the most important challenges to improve the service quality, attract and retain more customers, and reduce dealing with cash. Overcoming all these challenges would allow all citizens to have full access to financial services or in other words being financially included. Recently, Financial Inclusion has received higher priority to improve financial existing and reduce poverty on large scale. It is clear that due to the large scale of mobile phone access and the existing network, mobile money on of the most key enabler to financial inclusion. However, the differences of mobile money countries, characteristics, economy, adoption variables. This Paper analyzes the mobile money success factors from seven developing countries (Egypt, Kenya, Ghana, Tanzania, Uganda, Zimbabwe, and Rwanda) where there has been successful penetration of mobile money services in order to extract the determinants of mobile money services adoption. Mobile money adoption is affected by several factors that includes country specific characteristics, regulatory considerations, and service provision characteristics as a result nine independent variables were selected to be included in this research. Two dependent variables are chosen to present the mobile money adoption, these are registered subscribers ratio and active subscribers ratio. The analysis is based on the data collected from the central banks published statistics in each country of the above-mentioned seven countries. The analysis is achieved using panel data analysis for a sample of seven African countries for the period from 2013 to 2017. Data is analyzed using the linear regression model for each dependent variable of the mobile money adoption using nine explanatory variables. The statistical analysis is done using Eviews and least square (LS) estimation techniques are used to provide further strength for the results. The paper aims to define a model for measuring mobile money adoption and defining the impact of each of the mobile money adoption determinants on the adoption level. This could be used to define recommendations or strategic decisions for policy makers or mobile money service providers in Egypt to improve mobile money adoption.
Keywords: 330; Financial Inclusion; Mobile Money (MM); Mobile Money Services; Mobile Money Determinants; Registered subscribers ratio; Active subscribers ratio